1976
DOI: 10.1007/bf00606547
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of digitoxin in man and its modification by spironolactone

Abstract: The effect of spironolactone on the metabolism of intravenously administered 3H-digitoxin (80 muCi) was investigated in eight patients. In three of them the labelled glycoside was given on a second occasion after spironolactone treatment had been discontinued for at least 65 days. Of total urinary radioactivity 79% was unaltered drug and 12% consisted of water soluble compounds. No digitoxigenin or digoxigenin and only trace amounts (less than 2 %) of digoxin and the bis- and monoglycosides of digoxigenin were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1

Year Published

1978
1978
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(10 citation statements)
references
References 27 publications
1
8
1
Order By: Relevance
“…The half life of dt-3 is known to be shorter in patients treated with spironolactone (17) which indicates that such reactions may also occur in man. (The spironolactone effect cannot be explained by a higher rate of genin hydroxylation since the hydroxylated metabolites account for only a relatively small fraction of metabolites.)…”
Section: Discussionmentioning
confidence: 99%
“…The half life of dt-3 is known to be shorter in patients treated with spironolactone (17) which indicates that such reactions may also occur in man. (The spironolactone effect cannot be explained by a higher rate of genin hydroxylation since the hydroxylated metabolites account for only a relatively small fraction of metabolites.)…”
Section: Discussionmentioning
confidence: 99%
“…In a review of the clinical pharmacokinetics of digitoxin, Perrier et al (1977) reported a mean half-life of 7.6days, comparable to the mean values of 6.5 days (i. v.) and 5.8 days (oral) obtained in the current study using the specific assay (Table 2). In reported values for digitoxin elimination, shorter halflives were obtained when more specific assay methods were employed (Perrier et al 1977;Wirth et al 1976;Rasmussen et al 1971;Lukas 1971). In the current study, shorter mean half-lives were found using the specific compared to the non-specific assay, although this difference was not statistically significant (p < 0.05).…”
Section: Discussionmentioning
confidence: 93%
“…This could result in shortening the drug half-life and decreasing the toxicity, as previously observed. Wirth et al (1976) reported the effect of SL on the metabolism of i.v. administered [ 3 H]digitoxin in patients receiving SL chronically.…”
Section: Discussionmentioning
confidence: 99%
“…1978). It has been found that SL induces hepatic and intestinal microsomal drug metabolism enzymes in experimental animals (Feller and Gerald, 1971a,b;Stripp et al, 1971;Hamrick et al, 1973;Catania et al, 2003) and humans (Wirth et al, 1976;Miguet et al, 1980). SL has been shown to induce also specific membrane transport systems involved in organic anion uptake or secretion such as the organic anion transporter polypeptide 2 and multidrug resistanceassociated protein 2 in the rat (Guo et al, 2002;Ruiz et al, 2005).…”
mentioning
confidence: 99%